Corpus Papyrorum Judaicarum: Volume 4 - Hacham, Noah; Ilan, Ṭal (Corpus Papyrorum Judaicarum, 2020)
Frontmatter -- Acknowledgement -- Table of contents -- List of Abbreviations -- Explanatory Note -- Introduction -- Papyri of the Ptolemaic Period: Introduction -- Documentary papyri -- Literary Papyri -- Appendix 1: Additional Jewish papyri and ostraca -- Appendix 2: Ptolemaic inscriptions -- Appendix 3: Documents not considered Jewish and not included in N.CPJ IV -- Indices -- Table of Measurements -- Tables of sources, dates and locations of papyri in N.CPJ